Night-break treatment with blue and green lights regulates erect thallus formation in the brown alga Petalonia fascia (KU-1293) - Maegawa, Yuya; Takahashi, Fumio; Hiyama, Tsunami; Yoshikawa, Shinya (Frontiers in Plant Science, 2025)
In this study, we investigated the photoperiodic responses regulating erect thallus formation in Petalonia fascia (KU-1293). We found that, through critical day length analysis and night break treatment culture experiments, P. fascia formed erect thalli under short-day conditions, indicating a genuine photoperiodic response. The critical day length for this morphological change was 10–11 h. Notably, night-break treatment with blue light (BL) and green light (GL) inhibited, whereas that with red light (RL) enhanced erect thallus formation. P. fascia was more sensitive to BL than to GL, requiring approximately 100-times less light to exhibit similar effects. Furthermore, promotion of erect thallus formation by RL was not negated by far-red light, suggesting the presence of a novel RL receptor distinct from the classical phytochrome system in terrestrial plants. These findings highlight the complexity of light wavelength interactions in regulating photoperiodic responses and suggest the presence of unique photoreceptors for day-length perception and erect thallus formation in P. fascia.